Bio-analytical method for generic formulation: an IIUM pharmaceutical manufacturing plant experience - Helal Uddin, A.B.M. (2015)
Generic formulation of pharmaceutical dosage forms are emerging since the regulation of generic production of out of patent drug was implemented worldwide. Malaysian drug control authority has implemented policies to promote generic production in local pharmaceutical industries to reduce the burden of government expenditure due to importing patented drugs for internal use. IIUM Pharmaceutical Manufacturing Plant is a GMP compliant manufacturing plant. Beside academic objectives it is also aimed to produce generic formulation and eventually to be supplied to the health care institutes. Malaysian regulation requires bioequivalence study results (conducted in a local set up) for the registration of locally produced generic formulation. On that aspect our study was designed to cater this need. Bio-analytical method is defined as quantitative measurement of drugs in biological system (plasma, urine and tissues). It provides the specific evidence of the bioavailability of drugs. In this study we are reporting about the development of bio-analytical method of three generic formulations namely Amlodipine, Gliclazide and Mefenamic acid produced in this plant. One specific method was developed to determine Amlodipine (Antihypertensive) and Gliclazide (Anti-diabetic) in human plasma simultaneously. The aim of developing one method for both drugs is to reduce time and cost. Cetirizine was used as internal standard and the drugs were extracted from plasma using dichloromethane. The recovery was optimised using design of experiment software and the results showed that the recovery is 89%, 91% and 86% for amlodipine, gliclazide and cetirizine respectively. The unique characteristic of this method will enable to detect both drugs simultaneously or individually in plasma using HPLC system. Another study was designed to develop a rapid and sensitive method for the detection of mefenamic acid in human plasma. Protein precipitation technique using acetonitrile was used in the presence of diclofenac as internal standard. The recovery was found 83% for MA. The quality control samples of mefenamic acid which was termed as low (L), medium (M) and high (H) were analyzed to get the precision and accuracy. Over all accuracy for all the QC samples were above 90% which also reflects the recovery and the CV for the precision was lower than 10% for all the QC samples. Method developed for the bio-analytical assay of the generic drugs in human plasma formulated at IIUM pharmaceutical manufacturing plant is reported in this presentation. The method were found sensitive, economic, specific and reliable and in compliance with CDER (Centre for drug evaluation and research) guideline.